Analisis Faktor Metode Penginputan pada PT Sriwijaya Palm Oil Group Perkebunan Kelapa Sawit - Ice Novita Sari; Tata Sutabri (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Palm oil is one of the plantation commodities that is growing rapidly in Indonesia, with a total sales area of ​​11,672,861 ha in 2016. Clearing land for oil palm plantations is often carried out by converting forest land into plantation land. This activity has the impact of deforestation and is a serious threat. For biodiversity in Indonesia, orangutans are no exception. Orangutans are one of the animals that, based on the Assessment Information issued by the IUCN (International Union for Conservation of Nature and Natural Resources), orangutans are expected to be converted to Critically Endangered status in 2016. In the context of protecting orangutan habitat in Indonesia. Clearing of land for oil palm plantations is based on the instruments regulated in Law Number 32 of 2009 concerning Environmental Protection and Management and within the principles regulated in Minister of Agriculture Regulation Number 19 of 2011 concerning guidelines for oil palm plantations